Peran Pemberdayaan Ekonomi Pesantren Dalam Mendorong Kemandirian Ekonomi (Studi Kasus Pondok Pesantren Bahrul ‘Ulum Tambakberas Jombang) - Achmad Luthfi Chamidi (Jurnal Ilmiah Ekonomi Islam, 2023)
Boarding school as a non-formal, private Islamic educational institution whose existence has changed. Islamic boarding schools in their development and distinctive characteristics can improve the economy for both the pesantren and the surrounding community. The role of pesantren is to provide business opportunities, expand access and opportunities for students to apply the entrepreneurial spirit, and develop the position of pesantren as a center for community economic empowerment. The research method used is qualitative research. This type of research uses case studies. The results of this study are 1) Forms of economic empowerment of the Pesantren Bahrul Ulum Islamic Boarding School by; (a) Implementing an Ecoprotection system, (b) Establishing business units that are managed directly by Islamic boarding schools, namely Ibbien Mart, Ibbien Net, Ibbien Caffe, Ibbien Kantin, Ibbien Store, Baitul Maal al-Muhibbin, Ibbien Foods, Ibbien Wholesale, and Waste Banks. 2) The impact of economic empowerment of the Bahrul 'Ulum Islamic Boarding School which is occupied by Islamic boarding schools is able to assist in developing the education system and educational infrastructure without depending on any party, so as to be able to move the economy of the surrounding community economically independently and become a place for students to develop entrepreneurial knowledge through the business units they manage. 3) The role of economic empowerment of pesantren essentially refers to the conditions or results to be achieved by a social change, namely santri who are empowered to have the knowledge and ability to fulfill their physical, economic and social needs, such as having the confidence to be able to convey aspirations, have a good eye livelihood in increasing income, social activities, and being independent in carrying out their life tasks as students.